PERAN GURU BIMBINGAN KONSELING DAN ORANG TUA DALAM MENANGGULANGI PELANGGARAN SISWA DI MTs NW AIK AMPAT - Asror, Muhamad Alim Ka'batul; Nurjannah, N (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to see how the role of guidance and counseling teachers in schools and students' homes is so that violations committed by students can be prevented and how to know the role of parents themselves in controlling their children at home. As well as how the steps are taken in dealing with student violations at school and outside school. This research used a field study with a qualitative descriptive approach with data collection using observation, interviews, and documentation techniques and the validity of the data using triangulation and analysis using qualitative descriptive analysis. The results of this study indicate that the role of the Guidance Counseling teacher is very influential in fostering students so that they do not commit violations in the school environment as well as parents. In Overcoming Student Violations", religious teachers have the main task of teaching and have the mission of providing guidance and counseling to their students. Likewise, the primary mission of guidance and counseling teachers is to provide advice and counseling to students with problems. The provision of guidance assistance supplied by religious teachers is guidance in terms of students' religion, while guidance and counseling services provided by teachers are in terms of student psychology. Findings related to violations committed by students are still classified as minor violations that are still within the limits of violating school rules, including truancy, disrupting the process of teaching and learning activities, lack of discipline.